National Football League (NFL) quarterbacks who were multisport high school athletes have better in-season performance statistics and career success - Allahabadi, S.; Gatto, A. P.; Kopardekar, A.; Davies, M. R.; Pandya, N. K. (The Physician and Sportsmedicine, 2023)
Objectives To determine (1) the proportion of National Football League (NFL) quarterbacks (QBs) who were multisport high school athletes (2) whether performance metrics in NFL QBs differed by playing multiple high school sports versus the single sport of football.